2019
DOI: 10.1088/1757-899x/703/1/012045
|View full text |Cite
|
Sign up to set email alerts
|

Current Perspectives and Mini Review on Zeolitic Imidazolate Framework-8 (ZIF-8) Membranes on Organic Substrates

Abstract: Zeolitic Imidazolate Framework (ZIF) membranes have been considered as promising membrane for gas separation processes due to their robustness and good separation capabilities. The separation of hydrogen (H2) from larger gases is one of their potential applications. Among the different types of ZIF, ZIF-8 is considered as potential candidates for H2 separation owing to its small aperture size and excellent chemical stability. In recent years, ZIF-8 membranes have been fabricated on both inorganic and polymeric… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 32 publications
0
18
0
Order By: Relevance
“…In a different approach, Liu et al used the ZnAl-LDHs as a buffer for connecting the zeolitic-imidazolate framework-8 (ZIF-8) seed layer onto the Al 2 O 3 support and the wellintergrown ZIF-8 membrane was formed during the secondary growth [120]. Recently, ZIF-8 is incorporated on hollow fibre membrane in a laboratory scale continuous process [124,125], which shows a promising signal for commercial scale application of MOF membranes in the future.…”
Section: Metal Organic Framework (Mof) Membranesmentioning
confidence: 99%
“…In a different approach, Liu et al used the ZnAl-LDHs as a buffer for connecting the zeolitic-imidazolate framework-8 (ZIF-8) seed layer onto the Al 2 O 3 support and the wellintergrown ZIF-8 membrane was formed during the secondary growth [120]. Recently, ZIF-8 is incorporated on hollow fibre membrane in a laboratory scale continuous process [124,125], which shows a promising signal for commercial scale application of MOF membranes in the future.…”
Section: Metal Organic Framework (Mof) Membranesmentioning
confidence: 99%
“…Among ZIF materials, ZIF-8, which consists of Zn ions and 2-methylimidazolate with sodalite (SOD) topology, is undoubtedly the most extensively investigated ZIF. 18,19 Contradictory results on the water stability of ZIF-8 were reported in the literature. 16,20–23 While some early reports 16,20 suggested high water stability of ZIF-8 because there is no change in the X-ray diffraction (XRD) patterns of ZIF-8 crystalline powders after being placed in boiling water, an increasing number of studies demonstrated that ZIF-8 can partially degrade in aqueous solutions depending on the ZIF-8 to water mass ratio.…”
Section: Introductionmentioning
confidence: 99%
“…The bonding in ZIF is a coordination bonding that is weaker than covalent bonding in the zeolites thus leading to a kinetically lesser stable bond. This lesser stability enables the substitution by other ligands [13].…”
Section: Introductionmentioning
confidence: 99%